The American Flag - The Border Sentinel (Symphony in the Flint Hills, 2019)
Introduction: The following explanation of the colors and symbolic meaning of the “Stars and Stripes” was written by a member of the Constitutional Congress to whom, with others, was committed the duty of selecting a flag for the infant Republic. (Reprinted from: The Border Sentinel, Mound City, KS 6 May 1864.)